Effect of incision on visual outcomes after implantation of a trifocal diffractive IOL - Shasha Xue; Guiqiu Zhao; Xiaoni Yin; Jing Lin; Cui Li; Liting Hu; Lin Leng; Xuejiao Yang (BMC Ophthalmology, 2018)
Abstract Background To evaluate visual acuity, corneal astigmatism and corneal higher-order aberrations (HOAs) after implantation of trifocal diffractive IOLs operated with either a corneal steep-axis incision or 135° incision. Method This prospective study enrolled patients randomly assigned to different groups. According to preoperative corneal astigmatism, 101 eyes of 77 patients were assigned into group A1 (0 ~ 0.50 D) or A2 (0.51 ~ 1.00 D) with a corneal steep-axis incision or group B1 (0 ~ 0.50 D) or B2 (0.51 ~ 1.00 D) with a 135° incision. Visual acuity, corneal astigmatism and corneal higher-order aberrations (HOAs) were followed-up for 3 months. Results Corneal astigmatism in group A2 significantly decreased 3 months after surgery (P < 0.01) and was significantly lower than that in group B2 1 day, 2 weeks, 1 month, and 3 months postoperatively (all values of P < 0.01). The following parameters were better in group A2 than in group B2: uncorrected intermediate visual acuity (UIVA) at 1 day, 2 weeks, 1 month, and 3 months (P = 0.00, 0.00, 0.01, 0.01, respectively);uncorrected distance visual acuity (UDVA) at 1 day and 2 weeks (P = 0.00, 0.01); and uncorrected near visual acuity (UNVA) at 1 day, 2 weeks, and 1 month postoperatively (P = 0.00, 0.01, 0.02, respectively). Conclusions After a corneal steep-axis incision, patients with preoperative corneal astigmatism of 0.51 D to 1.00 D exhibited reduced corneal astigmatism and achieved better UIVA and early postoperative UDVA/UNVA. Trial registration Retrospectively Registered Trials ISRCTN10086721, 23/06/2018.